Typical and Atypical Antipsychotic Drugs Increase Extracellular Histamine Levels in the Rat Medial Prefrontal Cortex: Contribution of Histamine H1 Receptor Blockade - Svensson, Kjell A. (Frontiers in Psychiatry, 2012)
Atypical antipsychotics such as clozapine and olanzapine have been shown to enhance histamine turnover and this effect has been hypothesized to contribute to their improved therapeutic profile compared to typical antipsychotics. In the present study, we examined the effects of antipsychotic drugs on histamine (HA) efflux in the mPFC of the rat by means of in vivo microdialysis and sought to differentiate the receptor mechanisms which underlie such effects. Olanzapine and clozapine increased mPFC HA efflux in a dose related manner. Increased HA efflux was also observed after quetiapine, chlorpromazine and perphenazine treatment. We found no effect of the selective 5-HT2A antagonist MDL100907, 5-HT2c antagonist SB242084 or the 5-HT6 antagonist Ro 04-6790 on mPFC HA efflux. HA efflux was increased following treatment with selective H1 receptor antagonists pyrilamine, diphenhydramine and triprolidine, the H3 receptor antagonist ciproxifan and the mixed 5HT2A/H1 receptor antagonist ketanserin. The potential novel antipsychotic drug FMPD, which has a lower affinity at H1 receptors than olanzapine, did not affect HA efflux. Similarly, other antipsychotics with lower H1 receptor affinity (risperidone, aripiprazole and haloperidol) were also without effect on HA efflux. Perfusion of clozapine and pyrilamine into the TMN, but not the mPFC, increased local HA efflux. Finally, HA efflux after antipsychotic treatment was significantly correlated with affinity at H1 receptors whereas 9 other receptors, including 5-HT2A, were not. These results demonstrate that both typical and atypical antipsychotics increase mPFC histamine efflux and this effect may be mediated via antagonism of histamine H1 receptors.